Membrane fouling of actual extracellular polymeric substances. Issue 1 (January 2021) - Li, Qiang; Hu, Ge; Song, Peng; Khaliunaa, Natsagdorj; Khurram, Rooha; Zhang, Hu; Liu, Xuguo; Wang, Zhan; Gao, Shujuan; Liu, Chao; Wang, Xi
Abstract: Extracellular polymeric substances (EPSs) in activated sludge suspensions are the key substances leading to the membrane fouling. In order to understand the effect of EPSs on the membrane fouling, the actual EPSs solution extracted from activated sludge suspensions was used as the feed solution to conduct dead-end microfiltration experiment under different pressures by using different membranes. The flux ( J ), fouling resistances ( Rm, Rp, Rc and Rtotal ) and the available membrane area ( A/A0 ) were used to describe the membrane fouling. The results showed that with the increase of pressure, J and Rtotal increased. Rp firstly increased and then kept constant, Rc always increased and became the dominant resistance. A/A0 decreased from 1 to a constant. Rc plays a key role on Rtotal for different membranes under the same pressure. The sequence of the steady available membrane area ( A steady / A0 ) for different pressures was: 63.0% (0.05MPa)> 56.5% (0.08MPa)> 53.6% (0.10MPa), and that for different membranes was: 80.1% (0.2μm PES) > 79.9% (0.1μm PES) > 78.4% (0.1μm PAN) > 53.6% (0.1μm PVDF).